PERAN DAN STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI ERA COVID-19 - Sumarno, Sumarno; Sriyanto, Agus (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2021)
Principals as leaders have a very important role in maintaining the quality of education in schools. The Covid-19 pandemic has had a significant impact on the learning process in schools so that the quality of education in schools has decreased. For this reason, school principals must have the right role and strategy to maintain the quality of education during the Covid-19 pandemic. The purpose of this study was to find out the role and strategies carried out by the principal of SDIT Al-Jabar Sragen in maintaining the quality of education during the Covid-19 pandemic. The method used in this research is descriptive qualitative explanatory, namely digging information using structured interviews with the principal as a resource person. Information analysis used in this research is data reduction, presentation, and drawing conclusions. The results of this study indicate that; 1). The principal's role is as an educator, manager, administrator, supervisor, leader, innovator, and motivator. 2). in ensuring the quality of education is done through 3 main things, namely a). development of Learning Management System, b). LMS usage training, c). online teacher performance assessment. 3). The strategies carried out by the head of SDIT Al-Jabar Sragen in improving the quality of education are: a) Increasing the professionalism of teachers by providing online learning training such as zoom, googlemeet. b) Conducting workshops on making learning materials in the form of videos and uploading them on YouTube. c) Conducting a learning model with an at home in class system. d) Conduct coordination meetings with parents, school committees and related parties for the continuity of learning. e) Implement health protocols and provide vaccines for all school residents. Keywords; the role of principal, LMS, education quality strategy, covid-19, SDIT Al-Jabar Sragen